Caribbean cooperation in health : project profiles (CARICOM Secretariat GeorgetownGY, 1988)
Groups project profiles according to six priority areas viz. environmental protection; human resources development; chronic diseases; strengthening of health systems; food and nutrition; and mother and child health. Each profile has sub-headings including the priority area, project title, problem description, project description, project objectives, components, budget, associated institutions/agencies, duration, and remarks. Contains sub-groupings based on the geographic scope of the project. The geographic categories include the Caribbean, Eastern Caribbean and the individual CARICOM countries.
IDS